On the Ontology of Archaeology. (24th September 2015) - Moore, Lawrence
Abstract : Being an archaeologist requires social legitimization and acceptance within a community of archaeological practice. The term "archaeologist" is unsettled at an abstract level but is well defined in local contexts. A sociological definition is offered for "archaeologist" that is based upon a philosophical understanding of "archaeology." Archaeology has qualities that make it special and only those willing to advance through accepted legitimating processes achieve the title "archaeologist." Thus, not everyone should be an archaeologist.